An Approach to Maximize Retrograde Transport Based on the Spatial Distribution of Motor Endplates in Mouse Hindlimb Muscles - Xu, Jianyi; Xuan, Ang; Liu, Zhang; Li, Yusha; Zhu, Jingtan; Yao, Yingtao; Yu, Tingting; Zhu, Dan (Frontiers in Cellular Neuroscience, 2021)
Knowledge regarding the relationship between muscles and the corresponding motor neurons would allow therapeutic genes to transport into specific spinal cord segments. Retrograde tracing technique by targeting the motor endplate (MEP), a highly specialized structure that offers direct access to the spinal motor neurons, has been used to elucidate the connectivity between skeletal muscles and the innervating motor neuron pools. However, current injection strategies mainly based on blind injection or the local MEP region might lead to underestimation of the motor neuron number due to the uneven distribution of MEP in skeletal muscles. In this work, we proposed a novel intramuscular injection strategy based on the 3D distribution of the MEPs in skeletal muscles and applied the 3D intramuscular injection to the gastrocnemius and tibialis anterior for retrograde tracing of the corresponding motor neurons and compared with the existing injection strategy. The intramuscular diffusion of the tracer demonstrated that 3D injection could maximize the retrograde transport by ensuring greater uptake of the tracer by the MEP region. In combination with optical clearing and imaging, we performed 3D mapping and quantification of the labeled motor neurons and confirmed that 3D injection could label more motor neurons than the current injection method. It is expected that 3D intramuscular injection strategy will help elucidate the connective relationship between muscles and motor neurons faithfully and becomes a promising tool in the development of gene therapy strategies for motor neuron diseases.